2017
DOI: 10.31234/osf.io/k6tvg
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

If, Why, and When Subjective Well-Being Influences Health, and Future Needed Research

Abstract: We review evidence on whether subjective well-being (SWB) can influence health, why it might do so, and what we know about the conditions where this is more or less likely to occur. This review also explores how various methodological approaches inform the study of the connections between subjective well-being and health and longevity outcomes. Our review of this growing literature indicates areas where data are substantial and where much more research is needed. We conclude that SWB can sometimes influence he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 148 publications
(159 reference statements)
1
14
0
Order By: Relevance
“…Those with higher well‐being are then more satisfied with their lives, have higher levels of PA, and lower levels of NA. Evidence from a growing number of longitudinal, ambulatory, and experimental studies suggests that these facets of subjective well‐being are causal factors in better physical health (Diener, Pressman, Hunter, & Delgadillo‐Chase, ; Lyubomirsky, King, & Diener, ). Happier people tend to live longer (Diener & Chan, ) and to have better cardiovascular health (Boehm, Vie, & Kubzansky, ) and stronger immune systems (Marsland, Cohen, Rabin, & Manuck, ).…”
Section: Introductionmentioning
confidence: 99%
“…Those with higher well‐being are then more satisfied with their lives, have higher levels of PA, and lower levels of NA. Evidence from a growing number of longitudinal, ambulatory, and experimental studies suggests that these facets of subjective well‐being are causal factors in better physical health (Diener, Pressman, Hunter, & Delgadillo‐Chase, ; Lyubomirsky, King, & Diener, ). Happier people tend to live longer (Diener & Chan, ) and to have better cardiovascular health (Boehm, Vie, & Kubzansky, ) and stronger immune systems (Marsland, Cohen, Rabin, & Manuck, ).…”
Section: Introductionmentioning
confidence: 99%
“…As pointed above, this strong association can be explained on the basis of several transmission channels. First, there are physiological mechanisms, which indicate that happiness is beneficial for several systems of the human body, such as cardiovascular, immune and endocrine systems 8. Second, happy individuals tend to adopt healthy behaviours, and avoid unhealthy lifestyle.…”
Section: Discussionmentioning
confidence: 99%
“…After stratifying the sample by educational level or SES, we find that happiness significantly influences SRH in low-SES individuals, but this association wanes for the higher socioeconomic strata. A recent review noted that research findings might be moderated by the population that is studied, and there may thus be differences in the relationship between happiness and health across different population groups 8. For instance, a study found that anger is linked with subclinical atherosclerosis in low-SES individuals, but this is not the case for high-SES ones 13.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations